2014
DOI: 10.1002/hc.21189
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Quinolines and Indoles: Sulfur‐Assisted or Selenium‐Catalyzed Reaction of β‐(2‐Nitrophenyl)‐α,β‐unsaturated Ketones with Carbon Monoxide

Abstract: A simple and selective synthetic method of quinolines and indoles by the reaction of β‐(2‐nitrophenyl)‐α,β‐unsaturated ketones with carbon monoxide was developed. When β‐(2‐nitrophenyl)‐α,β‐unsaturated ketones were allowed to react with carbon monoxide and water in the presence of a stoichiometric amount of sulfur or a catalytic amount of selenium, the corresponding quinolines were produced in moderate‐to‐good yields. On the other hand, in the absence of water, the indoles were produced by the selenium‐catalyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
(16 reference statements)
0
6
0
1
Order By: Relevance
“…We found that the chalcone with the nitro group at the ortho position develops the strongest anti-inflammatory protective effect, whereas the chalcone with the nitro group at the para position, showed the smallest effect [14]. Another important aspect of Crystals 2021, 11, 1589 2 of 12 some nitro chalcones is that they can be used as intermediates for synthesizing various heterocyclic compounds like indoles, thioaurones, carbazoles, sultams, benzothiophenes, quinolines and indolin-3-ones [15][16][17][18][19][20][21][22][23]. On the other hand, the nitro chalcones also find application as chemosensors for anion sensing [24].…”
Section: Introductionmentioning
confidence: 94%
“…We found that the chalcone with the nitro group at the ortho position develops the strongest anti-inflammatory protective effect, whereas the chalcone with the nitro group at the para position, showed the smallest effect [14]. Another important aspect of Crystals 2021, 11, 1589 2 of 12 some nitro chalcones is that they can be used as intermediates for synthesizing various heterocyclic compounds like indoles, thioaurones, carbazoles, sultams, benzothiophenes, quinolines and indolin-3-ones [15][16][17][18][19][20][21][22][23]. On the other hand, the nitro chalcones also find application as chemosensors for anion sensing [24].…”
Section: Introductionmentioning
confidence: 94%
“…Nishiyama et al. developed a simple and selective synthetic method for quinolines 643 in moderate to good yields by the reductive cyclization of β‐(2‐nitrophenyl)‐α,β‐unsaturated ketones 642 with carbon monoxide, elemental sulfur and water (Scheme ) …”
Section: Sulfur As Catalystmentioning
confidence: 99%
“…(11)] [110] and quinolines from 2-nitrochalcones [Eq. (12)] [111,112] have been reported. In the latter case, the intermediacy of the aniline obtained via WGSR reduction was suggested by a set of clever competition experiments.…”
Section: The Water-gas Shift Reaction In Organic Synthesismentioning
confidence: 99%